Parametric Analysis of Multi-Span Cable-Stayed Bridges Under Alternate Loads - Hiram Arellano; Roberto Gomez; Dante Tolentino (The Baltic Journal of Road and Bridge Engineering)
The influence of the stiffness of piers, pylons and deck in the behaviour of multi-span cable-stayed bridges under alternate live loads is analysed. The variation of these parameters is discussed considering both a harp cable system and a fan cable system. Different types of connections between pier-pylon and deck are also considered. Based on the behaviour of a three-span cable-stayed bridge, the variation of pier-pylon stiffness and deck stiffness was analysed. A similar state of stress and deflections was obtained for both a three-span and a multi-span cable-stayed bridge. The study shows that the harp type system presents advantages compared to fan type in terms of its behaviour under alternate live loads considering the same values of deck stiffness and pier-pylon stiffness. It is demonstrated that the resistant mechanism of multi-span cable- stayed bridges is provided by the pier-pylon element.